Does copying idioms promote their recall?. Issue 2 (17th February 2016) - Stengers, Hélène; Deconinck, Julie; Boers, Frank; Eyckmans, June
Abstract : This paper reports an experiment designed to evaluate an attempt to improve the effectiveness of an existing L2 idiom-learning tool. In this tool, learners are helped to associate the abstract, idiomatic meaning of expressions such as jump the gun (act too soon) with their original, concrete meaning (e.g. associating jump the gun with the scene of a track athlete who starts running before the starting pistol is fired). This association lends concreteness to target lexis, which is known to facilitate learning (Paivio, A., & Desrochers, A.(1979) . Effects of an imagery mnemonic on second language recall and comprehension. Canadian Journal of Psychology, 33, 17–28). It is a mental operation that orients the learner first and foremost to the semantic dimension of the expression, however. It does not as such engage the learner with formal properties of the expression, such as its orthography. In an effort to stimulate the latter engagement, a copy exercise was incorporated in the learning procedure. The merit of this additional exercise was evaluated by having one group of students ( N = 21) study 25 idioms according to the new procedure, while a comparison group ( N = 21) was given an additional meaning-oriented task instead. Recall by the two groups was compared immediately and two weeks after the treatment by means of a gap-fill test. The copy exercise was not found to promote better recall, a result we discuss with reference to levels of processing theory (Lockhart, R.S., & Craik, F.I.G.(1990) . Levels of processing: A retrospective commentary on a framework for memory research. Canadian Journal of Psychology, 44, 87–112).